Efeito do cigarro na nefrotoxicidade crônica causada pela Ciclosporina A em ratos - Alves, Sueli Aparecida (2012)
Chronic nephrotoxicity induced by cyclosporine A (CsA) is characterized by renal dysfunction and irreversible tubulointerstitial fibrosis. Associated with the use of CsA, the habit of smoking is a risk factor that reduces the glomerular filtration rate, renal vascular resistance increases, deteriorating renal function and also causes morphological changes such as glomerulosclerosis and tubulointerstitial damage. Objective: The aim of this study was to assess the effects of previous cigarette smoke exposure on CsA-induced renal functional and structural changes in a consistent experimental model of chronic CsA nephrotoxicity. Methods: Wistar male Munich-Wistar, 180-200 g were divided into four groups of 10 animals (CsA/SC, CsA/S, VH/SC and VH/S) were exposed to cigarette smoke (Smoke chamber - SC) or sham procedure (chamber without smoke cigarettes - S) for 10 minutes twice a day for 20 weeks, with three cigarettes each exposure. Received a low sodium diet from 16 th to 20 th week and at week 17 was administered to CsA (2.5 mg/kg/day subcutaneously) or vehicle (VH) for 28 days. After 24 hours the last injection, the animals were anesthetized and the following studies: renal glomerular filtration - RGF (inulin clearance), renal blood flow - RBF and renal vascular resistance - RVR (Doppler ultrasound), renal histology (% System Merz), CsA blood level (radioimunoensaio, ng / ml) and immunohistochemistry for α-SMA, vimentin and nitrotyrosine. Statistical analysis: Results are presented as mean ± SD. ANOVA + Newman-Keuls test or Kruskal-Wallis test + Dunn. Statistical significance was set at P < 0.05. Results: The group that used CsA decreased in GFR (CsA/SC 0,39 ± 0,03 vs VH 0,83 ± 0,15 vs CsA/S 0,53 ± 0,05; ***p<0,001), the RBF (CsA/SC 3,9 ± 0,4 vs VH 6,7 ± 1,0 vs CsA/S 3,8 ± 0,6; p < 0,001) and increased RVR (CsA/SC 26 ± 2 vs VH 17 ± 3 vs CsA/S 27 ± 3; p < 0,001). There was also an increase of interstitial fibrosis (CsA/SC 17 ± 3 vs VH 3 ± 2 e CsA/S 21 ± 8 vs VH 3 ± 2; p<0,001), expression of tubulointerstitial α-SMA (CsA/SC 1,8 ± 0,3 vs VH 0,8 ± 0,3 vs CsA/S 1,7 ± 0,4; p<0,001) and periglomerular α-SMA (CsA/SC 1,0 ± 0,4 vs VH 0,3 ± 0,3, p < 0,001, CsA/S 0,5 ± 0,1 vs VH 0,3 ± 0,1; p<0,05) and expression of vimentin (CsA/SC 0,4 ± 0,4 vs VH 0,0 ± 0,0; p < 0,05 e CsA/S 0,5 ± 0,6 vs VH 0,0 ± 0,0; p < 0,01) and nitrotyrosine (CsA/SC 3 ± 0,3 vs VH 2,3 ± 0,4; p<0,01). With the use of tobacco, worsened in the fall of GFR (CsA/SC 0,4 ± 0,03 vs CsA/S 0,5 ± 0,0; *p<0,05), increased expression of α-SMA periglomerular (CsA/SC 1,0 ± 0,4 vs CsA/S 0,5 ± 0,1; p<0,01) and nitrotyrosine (CsA/SC 3 ± 0,3 vs CsA/S 2 ± 0,2; p<0,05). Conclusion: In conclusion, CS aggravated significantly CsA-induced GFR impairment, periglomerular structural lesion and oxidative stress in a rat model of CsA nephrotoxicity.